Determinants of cooperative membership in Iloilo City the case of Saint Joseph the Worker multi-purpose cooperative. - Cordova, Lovella Marie Bugna
Cooperatives are widely recognized as a successful agency towards development of the communities. These organizations help alleviate poverty by providing members better income opportunities, as well as affordable goods and services., The paper aimed to determine the socioeconomic factors that influence the decisions of residents of Jaro, Iloilo specifically Barangay Sambag and San Isidro in joining Saint Joseph the Worker Multi-Purpose Cooperative. There were two sets of participants in the study: fifty-nine (59) cooperative members and (60) non-members who were chosen through random sampling. Two sets of interview schedules were used during the field survey: one for cooperative members and another one for non-cooperative members. The data were analyzed using descriptive statistics and Logistic Regression analysis is conducted to identify the determinants of cooperative membership. The results showed that majority of the participants who are cooperative members are females, married, and college graduates. In terms of employment, nearly half of them are self-employed and most receive an income of P1,000-P5,000 per month. The independent variables considered to affect the decision of an individual to join the cooperative were identified by the researchers based on literature. These are the following: age, civil status, educational attainment, household size, income and sex. On the other hand, cooperative attributes such services, contribution, influence, background information and reputation were also considered. The results of this study reveal that the most significant variables that affect cooperative membership are the contribution and benefits that the cooperative offers, the background information that one has about the cooperative, the reputation of the cooperative as perceived by the residents, civil status and monthly income.